2017
DOI: 10.1002/ajh.24770
|View full text |Cite|
|
Sign up to set email alerts
|

Feasibility trial for primary stroke prevention in children with sickle cell anemia in Nigeria (SPIN trial)

Abstract: The vast majority of children with sickle cell anemia (SCA) live in Africa, where evidence-based guidelines for primary stroke prevention are lacking. In Kano, Nigeria, we conducted a feasibility trial to determine the acceptability of hydroxyurea therapy for primary stroke prevention in children with abnormal transcranial Doppler (TCD) measurements. Children with SCA and abnormal non-imaging TCD measurements (≥ 200 cm/s) received moderate fixed-dose hydroxyurea therapy (~20 mg/kg/day). A comparison group of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 30 publications
1
34
0
1
Order By: Relevance
“…(TWiTCH and SWiTCH trials), although less efficacious in the case of secondary stroke prevention. 47,48 Further, in a prospective feasibility clinical trial (SPIN) in Nigeria, hydroxyurea therapy resulted in significant decrease in transcranial Doppler (TCD) velocities >170 cm/s as well as improvement in the hematological profile of children with SCA. 49 Hence, hydroxyurea may provide an effective approach to primary stroke prevention, thus providing a feasible substitute for primary stroke prevention in low-income countries.…”
Section: Hydroxyurea Therapymentioning
confidence: 99%
“…(TWiTCH and SWiTCH trials), although less efficacious in the case of secondary stroke prevention. 47,48 Further, in a prospective feasibility clinical trial (SPIN) in Nigeria, hydroxyurea therapy resulted in significant decrease in transcranial Doppler (TCD) velocities >170 cm/s as well as improvement in the hematological profile of children with SCA. 49 Hence, hydroxyurea may provide an effective approach to primary stroke prevention, thus providing a feasible substitute for primary stroke prevention in low-income countries.…”
Section: Hydroxyurea Therapymentioning
confidence: 99%
“…To decrease life-long morbidity and mortality associated with strokes in children with SCA, our team initiated a primary stroke prevention trial using hydroxyurea therapy for children with SCA, 5 to 12 years of age (NCT02560935) living in Kano Nigeria. 5 Since 2012, our stroke prevention program in children with SCA has matured to include neighboring states to Kano in northern Nigeria, Katsina and Kaduna. Two initial steps were required to establish a regional stroke prevention program in these low-resource settings; 1) assessment of children with SCA requiring TCD screening;…”
mentioning
confidence: 99%
“…Comparably, in studies of patients with SCA and abnormal TCD from Nigeria, children who took hydroxyurea did not experience excessive toxicity compared with those not treated with hydroxyurea. 49,52 Furthermore, studies from other resource-limited settings in India, [53][54][55] Brazil, 56 Jamaica, 48,57,58 56 and Ferster et al 6 observed mean hemoglobin increases of 0.3 and 0.6 g/dL, respectively. In contrast, studies such as the HUG-KIDS trial that gradually increased hydroxyurea to maximum tolerated dose in all subjects reported higher hydroxyurea-induced HGB and MCV than those found in our study.…”
Section: Hematological Toxicitymentioning
confidence: 96%